2021
DOI: 10.1371/journal.pone.0254457
|View full text |Cite
|
Sign up to set email alerts
|

The parametric study of hybrid nanofluid flow with heat transition characteristics over a fluctuating spinning disk

Abstract: The study explored the 3D numerical solution of an unsteady Ag-MgO/water hybrid nanofluid flow with mass and energy transmission generated by a wavy rotating disc moving up and down. The nanofluid is generated in the context of Ag-MgO nanomaterials. Magnesium oxide and silver nanoparticles have been heavily reported to have broad-spectrum antibacterial operations among metal oxides and metals. Silver nanoparticles are without a doubt the most commonly used inorganic nanoparticles, with numerous innovations in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…Zhang et al . 14 used PCM to investigate the momentum and energy transfer formed by a wavy fluctuation of the surface. Algehyne et al .…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al . 14 used PCM to investigate the momentum and energy transfer formed by a wavy fluctuation of the surface. Algehyne et al .…”
Section: Introductionmentioning
confidence: 99%
“…Ullah et al 41 investigated how a hybrid nanofluid flow on the outside of a revolving disc could improve mass and heat conduction. They observed that hybrid nanofluids are more successful at transporting heat than regular nanofluids 42 46 . discuss the further uses, synthesis, utilization, and structural characteristics of magnetic nanomaterials and carbon nanotubes.…”
Section: Introductionmentioning
confidence: 99%
“…Silica is one of the most abundant class of compounds, and because of its inexpensive cost of manufacture, high surface area, and wettability, it has the potential to be an outstanding choice for commercial usage [25,26]. Zhang et al [27] inspect the entropy maximization in a hydromagnetic HNF flow of SiO2 and (MoS2 (molybdenum disulfide) NPs flowing toward a stretchy surface. Ahmed et al [28] inspect the Ag-MgO HNF flow with heat propagation generated by a curved spinning disc that rotates in three dimensions, both vertically and horizontally.…”
Section: Introductionmentioning
confidence: 99%